Arqueologia da paisagem nas dunas holocênicas : o estudo de caso do Sítio Cardoso (Lagoa Redonda, Pirambu, SE) - Simões, Fernanda Libório Ribeiro (2014)
The focus of this work is on characterization of occupations precolonial in the Holocene dunes, in other words, formed from and built upon the Holocene Marine Terrace. To develop the proposed theme we chose to analyze the archaeological site Cardoso. Located in the newly presented Sapucaia River Basin, which before would be the boundary between the River Basin of Japaratuba River and the São Francisco River, between two fixed dunes, delimited by the Lagoa Redonda spillway and the plain seaside. Therefore, the overall objective of this dissertation is to understand the occupation of the Sergipe coast by the implantation of precolonial groups in Holocene dunes, considering the bias of Archaeology Landscape. The specific objectives were designed to meet the details regarding the theme worked, where they are divided between (1) Conducting of literature survey on the paleoenvironment period of formation of the physical landscape; (2) Questioning the functionality of coastal sites for groups that occupied them, and (3) analyzing the deployment of sites in the landscape, a perspective microespacial (intrassites), mesoespacial (between landscape and sites) and macroespacial (region). The results obtained (four archaeological sites) were analyzed facing a discussion of the landscape and were identified the visibility strategies based on analysis of the ithic material's spatial distribution analysis, mobility and acquisition of the different raw materials and testing of ceramic material.